How venture capital thwarts innovation. - Stuck, B.
This paper address the question of whether venture capital funding has helped to promote or stunt the growth of technological innovation over the past decade. A study of 1,303 electronic high-tech initial public offerings for a 10-year period ending in 2002 showed that the level of innovation during the decade was surprisingly low. The results also did not correlate well with venture capital funding, i.e., the level of innovation actually dropped sharply after 1996, even as venture funding was rising. The paper presents four basic factors that can be attributed to the decrease in innovation.
Keywords: Internet; Lucent Technologies Inc; VC-funded start-ups.; E-commerce business models; Innovation management; Organizational structures; Venture capital